Association of early surgery and post-operative complications in patients with infective endocarditis. (3rd May 2023) - Manikantan, P; Tao, M; Despotidis, G; Rahman, T; Mann, N; Pyo, R
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Infective endocarditis (IE) is a disease associated with high risk of morbidity and mortality. Recent literature suggests that surgery during index hospitalization may be performed safely without increased risk of mortality. However, the risk of post-operative complications remains unclear. Purpose: The purpose of this meta-analysis is to assess the association of early surgery with post-operative complications as compared to delayed surgery in patients with IE. Methods: We performed a literature search for studies reporting an association between early surgery and study endpoints. The primary endpoint was post-operative neurological complications. The secondary endpoints were post-operative systemic embolic events, recurrence of IE, and need for reoperation. Early surgery was defined as surgery within 14 days of admission. The search included the following databases: Ovid MEDLINE, EMBASE, Web of Science, and Google Scholar. The search was not restricted to time or publication status. Results: A total of 11 studies with 1857 participants (634 with early surgery vs 1223 with delayed surgery) were included. The mean duration of follow-up was 39 months (ranging between 6 to 66 months). Early surgery compared to delayed surgery was not associated with increased risk of post-operative neurological complications (OR 1.01, 95% CI 0.55, 1.85; P=0.98). Heterogeneity was low: Chi2 = 2.93, I2 = 0%. Early surgery compared to delayed surgery was not associated with increased risk for post-operative systemic embolic events, recurrence of IE, or need for reoperation (OR 0.98, 95% CI 0.6, 1.61; p=0.94; OR 1.66, 95% CI 0.83, 3.33; p=0.15; OR 2.18, 95% CI 0.41, 11.69; p=0.36). Conclusions: Early surgery performed within 14 days of initial hospitalization is not associated with increased risk of post-operative complications compared to delayed surgery. Early Surgery and Post-op Complications